Higher education internationalization: lessons from Korea and Singapore - Nguyễn, Thị Vân Hạnh (Đại học Quốc gia Hà Nội, 2020)
Internationalization of education in general and higher education in particular is a vital trend in this globalized world. Internationalization of higher education is seen as one of the way a country responds to the impact of globalization. Although national identity and culture are keys to higher education internationalization, learning from other countries is also very important to any nation who wants to success in internationalization of their higher education. Korea is a developed country in Asia and Singapore is one in Southeast Asia which have many common in ideology and culture with Vietnam. Both Korea and Singapore are quite successful in developing their internationalized higher education system. Those two countries’ experiences in internationalizing their higher education system may be some useful lessons for Vietnam. This paper will discuss on the following issues: Concept and approaches toward internationalization of higher education; Higher education internationalization in Korea; Higher education internationalization in Singapore; Lessons for Vietnam.